Subcultures and socialization - Peñaloza, Lisa (Henry Stewart Talks, 2013)
Definition of culture, Evolution of subcultures, Examples, Socialization, Subcultural identity, Subcultural community, Consumer and market subcultures, Teenagers, Latinos in the U.S.: social dynamics, Identity terminology, Key statistics, Market trajectory, Community challenges, Conclusion, Social fragmentation and market specialization, Apple, References